2003
DOI: 10.1098/rspb.2002.2273
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic cues and time of season affect fuel deposition in migratory thrush nightingales (Luscinia luscinia)

Abstract: Bird migration requires high energy expenditure, and long-distance migrants accumulate fat for use as fuel during stopovers throughout their journey. Recent studies have shown that long-distance migratory birds, besides accumulating fat for use as fuel, also show adaptive phenotypic flexibility in several organs during migration. The migratory routes of many songbirds include stretches of sea and desert where fuelling is not possible. Large fuel loads increase flight costs and predation risk, therefore extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 31 publications
(31 reference statements)
6
43
0
2
Order By: Relevance
“…The lack of a complete response in the experimental birds resembling natural fuelling patterns is probably due to constraints in the experimental set-up (for example the very fast change to the magnetic field of Egypt and the absence of all other natural cues birds will obtain during migration) (Kullberg et al, 2003). Corticosterone levels in birds are known to vary with social and environmental factors (Raof et al, 2006;Rubenstein, 2007;JenniEiermann et al, 2008), but observed seasonal variation in corticosterone levels has been suggested to be mediated through photoperiodically induced seasonal changes in physiology rather than variation in environmental factors like temperature, storms or habitat condition (Romero et al, 1997;Romero and Wingfield, 1998;Romero, 2002;Landys et al, 2004b;Romero and Rich, 2007;Holberton et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of a complete response in the experimental birds resembling natural fuelling patterns is probably due to constraints in the experimental set-up (for example the very fast change to the magnetic field of Egypt and the absence of all other natural cues birds will obtain during migration) (Kullberg et al, 2003). Corticosterone levels in birds are known to vary with social and environmental factors (Raof et al, 2006;Rubenstein, 2007;JenniEiermann et al, 2008), but observed seasonal variation in corticosterone levels has been suggested to be mediated through photoperiodically induced seasonal changes in physiology rather than variation in environmental factors like temperature, storms or habitat condition (Romero et al, 1997;Romero and Wingfield, 1998;Romero, 2002;Landys et al, 2004b;Romero and Rich, 2007;Holberton et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The magnetic field of northern Egypt was calculated according to IGRF 10th generation (International Association of Geomagnetism and Aeronomy, 2005). The chosen location in northern Egypt is based on autumn ring recoveries of thrush nightingales in the eastern Mediterranean area ringed in northern Europe, suggesting that they prepare for crossing the Sahara desert in a confined species-specific area (Fransson et al, 2005;Kullberg et al, 2003). In total eight birds were subject to the magnetic treatment and eight birds were used as controls.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that, in addition to having evolved a number of behavioral, physiological and morphological adaptations to the demands of migration, (Dawson et al 1983;Andrews 1995;McWilliams and Karasov 2001;Kullberg et al 2003;Mettke-Hofmann and Gwinner 2003;Wikelski et al 2003;Mouritsen and Ritz 2005;Pravosudov et al 2006) migratory birds have also evolved adaptations to combat the negative consequences of sleep loss. To date, however, evidence of potential mechanisms for sleep loss compensation in migratory birds is absent.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with a recent appraisal and study of spatio-temporal precision in bird migration. For instance, in an experimental study, Fransson et al (2001) and Kullberg et al (2003Kullberg et al ( , 2007 illustrated that birds may use geomagnetic cues as external indicators for successful migration, and they explain that these cues (simultaneously operating with bird's orientation behavior and endogenous rhythm) provide information about the geographical position when such information is required, for instance, for a fueling decision. Given this, depending on the species and the route taken, a certain relationship would be expected between body mass and latitude of a given geographic area.…”
Section: Body Mass Variation Among Latitudes and Migration Sectorsmentioning
confidence: 99%